Paradigm Changes of Pesantren: Community and Islamic Scholar Perception about Post-Modernism Pesantren based on Android - Prima Aswirna; Reza Fahmi; Ahmad Sabri; Darni Yusna (Fakultas Ilmu Pendidikan UNP)
Pesantren is the forerunner of education based in Indonesia. This study uses a quantitative approach. Population in this research is Padang city society (especially in District of Padang Utara). The study sample was 128 people and 30 community leaders (Alim-Ulama) people. The sample selection was done by simple random (simple random sampling). Data collection techniques using questionnaires. Data analysis technique using SPSS program version 24. Statistical analysis technique used is Pearson correlation. The results of the study found: there is no correlation between public opinion and religious figures about the development of pesantren based on android postmodernism. Recommendations: There needs to be a more in-depth study of the development of Android-based pesantren at the empirical level; curriculum, learning system, learning strategy and assessment mechanism and so on.